IMPLEMENTASI AUDIT MUTU INTERNAL, TINDAK LANJUT, DAN PEMBANGUNAN BUDAYA MUTU: STUDI KASUS DI SDIT JAISYUL QUR’AN BINEKAS KECAMATAN NAGREG - Siti Nuraisyah Warohmah; Mulyawan Safwandy Nugraha (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Educational quality assurance has become a strategic priority in ensuring sustainable school improvement, encompassing not only academic outcomes but also systemic processes and organizational culture. This study aims to analyze the implementation of internal quality audits, follow-up mechanisms, and the development of quality culture at SDIT Jaisyul Quran Binekas Nagreg. A qualitative case study approach was employed to explore the phenomenon in depth through interviews, observations, and document analysis. The findings reveal that internal audits have been conducted periodically; however, their function remains largely administrative and has not fully transformed into a continuous improvement instrument within the PPEPP cycle. Evidence collection has applied triangulation techniques, although it is still dominated by documentation rather than authentic classroom practices. Furthermore, follow-up actions are not yet systematically structured, limiting the effectiveness of corrective measures. The study also highlights that quality culture is gradually developing through leadership, routine communication, and the internalization of Islamic values such as amanah, ihsan, and itqan. These values strengthen teachers’ intrinsic motivation and institutional commitment to quality. Overall, the research formulates an integrative model that connects audit, follow-up, and quality culture within a sustainable system based on ethical and spiritual foundations.